OPTIMAL CONDITIONS OF INDUCTION OF L-AMINO ACID OXIDASE OF $ASPERGILLUS~NIGER$ R3 FUNGUS BY HYDROGEN PEROXIDE (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
Our previous research has shown that L-amino acid oxidase activity in Asp. niger R3 yeast extracts was not detected and only some peroxisomal fractions have L-amino acid oxidase activity. Induction of L-amino acid oxidase is seen when hydrogen peroxide is added to the growth media. Our task was to investigate the induction of the enzyme by H2O2 addition to incubation media. The results revealed that adding H2O2 to Asp. niger R3 yeast extracts induce L-amino acid oxidase, especially it is more effective to use H2O2 in the concentration of 0.001 μM in the case of L-alanine as a substrate, and in the case of L-methionine – 0.003 μM respectively.
Keywords: enzyme induction; L-alanine; L-methionine; deamination; inhibitory effect